EFFECT OF ZINC OXIDE NANOPARTICLES ON FEED EFFICACY OF MULBERRY SILKWORM, BOMBYX MORI (L.) (LEPIDOPTERA: BOMBYCIDAE) (International Journal of Food and Nutritional Sciences, 2022)
The silk industry has developed as a popular cottage industry providing selfemployment to more than ten million rural persons in the unorganized sector. Effortsare being made to evolve effective new technologies, that labor-saving and ecofriendly. The silkworm, Bombyx mori L